(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: This study aimed to evaluate knowledge and self-injection practices of insulin among outpatients with type 2 diabetes mellitus (T2DM) at Transport Hospital in 2022. Methods: A cross-sectional study was conducted on 100 randomly selected T2DM outpatients from June 1 to June 30, 2022. Data were collected using a 14-item questionnaire assessing knowledge (insulin storage, injection sites, adverse effects) and standardized checklists for syringe and pen injection techniques. Descriptive statistics were analyzed using SPSS 20.0. Results: Among participants, 57% were female, 43% male; 73% lived in urban areas and 58% had post-secondary education. Regarding knowledge, 81% correctly stored unopened insulin in a refrigerator, but only 56% stored opened vials appropriately; only 24% monitored expiry dates and 18% recorded the opening date. All patients identified abdomen, arm, and thigh as injection sites, while 75% recognized the buttock. Nearly all (98%) recognized hypoglycemia and 79% were aware of infection risk. In practice, with syringes, 80% performed hand hygiene, 91% disinfected before injection, 89% pinched skin, and 90% injected at the correct angle, but only 71% disinfected post-injection. With pens, 84% washed hands, 75% mixed insulin properly, 69% attached needles and disinfected correctly, 77% primed and held the needle long enough, but only 54% pinched the skin appropriately. Conclusions: While patients demonstrated basic knowledge and skills in insulin self-injection, gaps remain in expiry monitoring, documentation of vial opening, post-injection disinfection, and skin pinching when using pens. Standardized patient education emphasizing storage, site rotation, and safe injection techniques is recommended.